PERBEDAAN INDEPENDENSI AUDITOR TERKAIT TENUR AUDIT - Hari Kusuma Satria Negara (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2016)
This study examines whether there are differences in the level of auditor independence related to the restriction tenure audit by the government. Law No 5 of 2011 on Public Accountants providing audit tenure limit for an audit partner of three years and a maximum of six years for public accounting firm in a row and each public accounting firm. Code of Conduct auditor mentions some of the threats that may affect the independence of the auditor, namely: self-interest threats, self threats, advocacy threats, family threats, and intimidation threats. This study obtained questionnaire data from the Public Accounting Firm Partner in several major cities in Indonesia. Research using the Mann Whitney test with the test results showed no significant differences in auditor independence, but independence of the auditor's legal defense related threats that shows there is a difference between long-term audit tenur tenur short-term audit.  Keywords: Tenure audit, auditor independence.